2016
DOI: 10.1021/acssuschemeng.6b01244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnetic Lignin-Based Hollow Microspheres: A Highly Adsorptive and Reusable Adsorbent Derived from Renewable Resources

Abstract: Lignin, a byproduct of the wood-pulping industry, is mostly treated as a noncommercialized waste product. Therefore, it is significant to study its potential for the conversion of this renewable and sustainable resource into high-valued chemicals and materials. In this study, a renewable lignin-based material with high performance in wastewater treatment has been explored on account of its satisfactory properties and being environmentally friendly. Herein, lignin hollow microspheres (LHM) were facilely prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(53 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Therefore, these materials have been drawn great attention on the development of biomass adsorbents (Das et al, 2010;Guo et al, 2008). Among the biomass materials, lignin has many advantages of adsorption owing to the specific functional groups and spatial structure features (Dizhbite et al, 1999;Li et al, 2016a;Brandt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these materials have been drawn great attention on the development of biomass adsorbents (Das et al, 2010;Guo et al, 2008). Among the biomass materials, lignin has many advantages of adsorption owing to the specific functional groups and spatial structure features (Dizhbite et al, 1999;Li et al, 2016a;Brandt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, PHPLs exhibited greater adsorption capacity than PL, which was probably due to a relatively higher oxygen-containing functional groups content on PHPLs via oxidative modification. By contrast, MB adsorption capacities of lignins and lignin-based materials were 31.2-80.6 mg g −1 (see Table 4) [40,[42][43][44][45]. Thus, the excellent adsorption capacity of PHPLs made them in application more feasible.…”
Section: Adsorption Of Cationic Substances By Phplsmentioning
confidence: 97%
“…Among these adsorbents is lignin which is one of the most abundant organic polymers in plants, just behind cellulose (Chen 2014). Several studies (Zhingang et al 2017;Yinliang et al 2016;Adebayo et al 2014;Menkiti and Aniagor 2017) have reported the existence of various functional groups such as methoxyl, phenolic, carboxyl, aromatic, alcohol, hydroxyl, aldehyde, etc., in lignin. These available functional groups explain lignins' potential in the remediation of dye effluent.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications exist on the application of lignin in dye adsorption processes; study by Yinliang et al (2016) showed the comparison of lignin obtained from larch and poplar tree for the uptake of methylene blue Dye. Zhingang et al (2017) evaluated the uptake of methylene blue (MB) from simulated wastewater using Cortaderia selloana flower spikes and its carbon fiber derivative as adsorbents.…”
Section: Introductionmentioning
confidence: 99%